2014
DOI: 10.4172/plastic-surgery.1000869
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the aesthetic outcomes of prosthetic breast reconstructions that have complications

Abstract: B reast reconstruction can help moderate the distressing postoperative changes in body image and the quality of life of breast cancer patients undergoing mastectomy (1-4). In particular, the literature has shown aesthetic results following reconstruction to be a major contributor to patient satisfaction and overall quality of life (5). With numerous reconstruction techniques currently available, myriad studies have detailed the postoperative surgical and cosmetic outcomes of such methods. In addition, factors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In this review, 2 studies compared aesthetic outcomes of patients with autologous conversion to patients that completed prosthetic reconstruction [19,25] . Mioton et al [19] reported superior scores across 4 out of 5 domains evaluated (volume, contour, placement, and inframammary fold) in 18 patients with autologous conversion after complicated implant reconstruction as compared to 136 patients with uncomplicated prosthetic reconstruction.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this review, 2 studies compared aesthetic outcomes of patients with autologous conversion to patients that completed prosthetic reconstruction [19,25] . Mioton et al [19] reported superior scores across 4 out of 5 domains evaluated (volume, contour, placement, and inframammary fold) in 18 patients with autologous conversion after complicated implant reconstruction as compared to 136 patients with uncomplicated prosthetic reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…They reported a mean overall aesthetic score of 3.25, which was similar to the mean score of 3.28 in patients with non-irradiated implant reconstruction. A validated 3-point scale (0-2) of 5 distinct aesthetic domains was used by another study, which reported mean scores of 1.6 for volume, 1.6 for contour, 1.75 for placement, 1.80 for inframammary fold, and 1.35 for scarring in 18 patients who had autologous conversion after experiencing complication with initial expanderimplant reconstruction [19] . They reported superior scores across 4 of these domains (volume, contour, placement, and inframammarry fold) as compared to patients completed expander implant reconstruction without complication.…”
Section: Autologous Salvage Of Unsuccessful Prosthetic Breast Reconstmentioning
confidence: 99%
See 2 more Smart Citations
“…Given our ability to achieve these results consistently, predictably, and for the most part reproducibly, many women will focus on what many surgeons would consider minor irregularities. The reality is that contour abnormalities of the breast following prosthetic reconstruction are more common than surgeons realize and constitute the majority of complaints that women have [1]. A common contour abnormality is the scalloping that occurs along the upper lateral aspect of the breast at the junction of the device and the soft tissues.…”
mentioning
confidence: 99%